2017
DOI: 10.1515/polyeng-2017-0099
|View full text |Cite
|
Sign up to set email alerts
|

Study on the adhesive properties of reactive liquid rubber toughened epoxy-clay hybrid nanocomposites

Abstract: AbstractThe present work investigates the adhesive properties and morphology of diglycidyl ether of bisphenol A nanocomposites modified with reactive butadiene acrylonitrile copolymers having different amine equivalent weight. Tensile adhesive strength and shear adhesive strength of epoxy resin were significantly increased due to reactive rubbers and nanoparticles (ZW1) incorporation to the epoxy matrix. Hybrid composites based on 1 wt% ZW1 and 10 wt% ATBN-16, 1 wt% ZW1 and 15 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 25 publications
0
12
0
1
Order By: Relevance
“…However, due to the high crosslink density, they are relatively brittle and have poor resistance to crack initiation and growth which makes their applications to be limited in many areas . So far, various toughening agents have been used to improve the toughness of epoxy resins, among which rubber particles , thermoplastics , and rigid fillers can be named. Many attempts have been made to improve the toughness of the resins by the inclusion of carboxyl‐terminated butadiene acrylonitrile (CTBN) liquid rubber.…”
Section: Introductionmentioning
confidence: 99%
“…However, due to the high crosslink density, they are relatively brittle and have poor resistance to crack initiation and growth which makes their applications to be limited in many areas . So far, various toughening agents have been used to improve the toughness of epoxy resins, among which rubber particles , thermoplastics , and rigid fillers can be named. Many attempts have been made to improve the toughness of the resins by the inclusion of carboxyl‐terminated butadiene acrylonitrile (CTBN) liquid rubber.…”
Section: Introductionmentioning
confidence: 99%
“…However, the incorporation of 1 – 3 wt% nanobent improved K C parameter values by approximately 30 – 60% as compared with the unmodified resin. The increase of the mechanical properties of epoxy resin due to nanoparticles (nanobent) was largely reported in literature and attributed to the intercalation and exfoliation processes of nanolayers .…”
Section: Resultsmentioning
confidence: 93%
“…The results of the modeling were in good agreement with those obtained experimentally. Various studies investigated the preparation and properties evaluation of epoxy resin by a combination of both thermoplastic materials and nanolayered particles aiming at reaching synergism effect and hence improving fracture toughness and thermal resistance of the matrix .…”
Section: Introductionmentioning
confidence: 99%
“…An observation at magnification indicated that BAQPS tended to agglomerate, which is likely due to the smaller d-spacing compared to BAQAS. On the other hand, increasing the amount of these bentonites to 3 wt.% caused a significant change in the structure and the formation of morphology with a structure characteristic for composites containing modified aluminosilicates ( Figure 14 g–j) [ 67 , 68 ].…”
Section: Resultsmentioning
confidence: 99%